Asset Compliance Boosts the Effectiveness of Financial Risk Prevention and Control - Li, Yinge (Economics and Management Innovation, 2025)
With the increasing complexity of financial markets, asset compliance issues have gradually become one of the key factors affecting market stability. Analyze the impact of asset compliance on enterprise risk prevention and control mechanisms, financial market stability, and compliance governance effectiveness, and reveal how asset compliance enhances financial risk management capabilities. Enterprises and financial markets are chosen as research subjects because they are directly related to capital flows and market stability, and they face particularly prominent compliance challenges. At present, relevant research mainly focuses on the surface phenomena of asset compliance and market stability. However, the deep correlation between asset rule of law and capital compliance has not been fully explored. Based on methods such as model prediction, data-driven, and supervision mechanisms, this paper analyzes how asset compliance can effectively prevent and control financial risks by optimizing risk assessment, improving compliance management efficiency, and enhancing market transparency. Research has shown that the complexity of laws and regulations, the lack of compliance technology, and the imperfect regulatory system are the main challenges facing the current financial market. The research has deepened the understanding of the relationship between asset compliance and financial risk prevention and control mechanisms, providing a new perspective for compliance governance in the financial industry; Provides specific pathways for policy makers and financial institutions to optimize compliance management. There are also difficulties in obtaining data and limitations in the research sample. Future research can be further expanded to comparative analysis of different countries and markets to achieve more comprehensive risk prevention and control strategies.